Cross-linguistic perception of clearly spoken English tense and lax vowels based on auditory, visual, and auditory-visual information. (July 2020) - Redmon, Charles; Leung, Keith; Wang, Yue; McMurray, Bob; Jongman, Allard; Sereno, Joan A.
Highlights: Clear speech benefits depend on the phonetic contrast and the stimulus modality. Acoustic/visual modifications from clear speech conflict with vowel tensity cues. Natives and non-natives show a clear speech disadvantage on visual lax vowels. Results support cue-specific models of clear speech effects. Abstract: The effect of clear speech on the integration of auditory and visual cues to the tense-lax vowel distinction in English was investigated in native and non-native (Mandarin) perceivers. Clear speech benefits for tense vowels /i, ɑ, u/ were found for both groups across modalities, while lax vowels /ɪ, ʌ, ʊ/ showed a clear speech disadvantage for both groups when presented in the visual-only modality, with Mandarin perceivers showing a further disadvantage for lax vowels presented audio-visually, and no difference in speech styles auditorily. English perceiver responses were then simulated in an ideal perceiver model which both identified auditory (F1, F2, spectral change, duration) and visual (horizontal lip stretch, duration) cues predictive of the clear speech advantage for tense vowels, and indicated which dimensions presented the greatest conflict between cues to tensity and modifications from clear speech (F2 and duration acoustically, duration visually). Altogether, by combining clear speech acoustics, articulation, and perception into a single integrated framework we are able to identify some of the signal properties responsible for both beneficial and detrimental speech style modifications.